Reviewing the role of the environment in the talent development of a professional soccer club - Gesbert, Vincent (PLoS One, 2021)
This two-part study examined the perceptions of talented Swiss soccer players about their talent development environment. The first study presented the translation and validation of the Talent Development Environment Questionnaire (TDEQ) into French using a recommended methodology for translating and culturally adapting questionnaires. Two hundred and three Swiss athletes (M = 16.99 years old) responded to the 25 items of the TDEQ-5. One item was excluded due to low factor loadings, and the descriptive statistics showed that the re-specified TDEQ-5 instrument had acceptable global model fit according to the thresholds in the literature (χ2 (df = 17) = 484.62, p<0.001, CFI = 0.91, TLI = 0.90, RMSEA = 0.07, SRMR = 0.06). This adaptation is thus valid for assessing the effectiveness of talent development processes. For the second study, a holistic design was used to examine the perceptions of a set of players embedded in a top-level Swiss soccer academy (i.e., 64 elite soccer players from 14 to 18 years old) by using the TDEQ-5. The results showed some relative strengths (i.e., F1-Long-Term Focus for the M15 and M16 age-groups) and weaknesses (i.e., F2-Alignment of Expectations for the M17 and M18 age -groups and F3-Communication for M17). They also highlighted that the talent pathways of these Swiss soccer players could not be summarized by a single type of transition toward a professional team. Rather, there were context-specific requirements, such as the critical period between the M15-M16 and M17-M18 age-groups, suggesting that when the players first entered their TDE they experienced a set of affordances to develop and flourish, which thereafter were perceived as less rich and/or abundant. These results offer a starting point for optimizing talent pathways.